Data Request and Record Management System - NISEN SEGAR; Dr. NORYUSLIZA BINTI ABDULLAH (Applied Information Technology And Computer Science, 2026)
Effective data management is important for informed decision-making in organizations. The Academic Administration Office (PPA) at Universiti Tun Hussein Onn Malaysia (UTHM) faces challenges such as processing delays, human errors, and inefficient data request handling. This study aims to address these issues by developing a user-friendly PPA Data Request and Record Management System. The system was developed using the waterfall model by following detailed sequential phases. It streamlines data request management, reduces errors, enhances decision-making, and supports digital transformation, ultimately leading to effective data management practices.